Ecology and natural history of the Caribbean reef squid Sepiotheuthis sepioidea (Phylum Mollusca, Class Cephalopoda) - Ghadially, Melissa (MacEwan University Student eJournal, 2015)
Cephalopod molluscs evolved from ancient cephalopods found during the Cambrian period around 550 million years ago. The Caribbean reef squid (Sepiotheuthis sepioidea) is a small species of cephalopod, up to 30cm in length, found in the tropical and subtropical waters of the western Atlantic Ocean. Throughout their lives these squid can be found in various places in the water column and on the reef. Aside from being a predator, the Caribbean reef squid is also prey for many species of fish as well as humans. Global warming and potential fishing threats are altering the reef squid’s habitat.